Effects of home-based interventions using exergames on physical and cognitive functions in community-dwelling older adults: a PRISMA-P-compliant protocol for a systematic review - Seinsche, Julia; de Bruin, Eling D.; Hinrichs, Timo; Giannouli, Eleftheria (Frontiers in Public Health, 2024)
Introduction Physical activity and exercise are crucial to counteract physical and cognitive decline in old age. Home-based exergame training can be a solution to overcome physical inactivity. This systematic review aims to provide a comprehensive overview of home-based exergame interventions and evaluate their effectiveness in improving cognitive and physical functions through physical activity enhancement in older adults. Methods and analysis We are conducting a systematic literature search including studies examining (1) community-dwelling older adults aged 60 years and older without any specific disease, (2) exergame-based exercise programs that take place at least partially in a home setting, and (3) intervention-related physical and/or cognitive outcomes. We will include randomized controlled trials and any other type of pre-post study published in English. There are no restrictions in terms of control group type and publication date. A search string was created and used in PubMed, Web of Science, Embase, Scopus and CINAHL. In addition, a hand search is carried out. This involves checking the references of the included studies and searching Google Scholar for further studies. The included studies will be summarized and, if homogeneity is sufficient, a random-effects meta-analysis will be performed. We will assess the risk of bias using RoB 2.0 and ROBINS-I. Conclusion The findings of this systematic review will help to define the most suitable exergame programs to counteract cognitive and physical decline in older adults. Additionally, they will inform the development of effective home-based exergame systems and point to future pathways of digital rehabilitation in older adults. Registration Prospero (ID: CRD42023374234).